Immortalized Dorsal Root Ganglion Neuron Cell Lines - Haberberger, Rainer Viktor; Barry, Christine; Matusica, Dusan (Frontiers in Cellular Neuroscience, 2020)
Pain is one of the most significant causes of suffering and disability world-wide, and arguably the most burdensome global health challenge. The growing number of patients suffering from chronic pain conditions such as fibromyalgia, complex regional pain syndrome, migraine and irritable bowel syndrome, not only reflect the complexity and heterogeneity of pain types, but also our lack of understanding of the underlying mechanisms. Sensory neurons within the dorsal root ganglia (DRG) have emerged as viable targets for effective chronic pain therapy. However, DRG’s contain different classes of primary sensory neurons including pain-associated nociceptive neurons, non-nociceptive temperature sensing, mechanosensory and chemoreceptive neurons, as well as multiple types of immune and endothelial cells. This cell-population heterogeneity makes investigations of individual subgroups of DRG neurons, such as nociceptors, difficult. In attempts to overcome some of these difficulties, a limited number of immortalized DRG-derived cell lines have been generated over the past few decades. In vitro experiments using DRG-derived cell lines have been useful in understanding sensory neuron function. In addition to retaining phenotypic similarities to primary cultured DRG neurons, these cells offer greater suitability for high throughput assays due to ease of culture, maintenance, growth efficiency and cost-effectiveness. For accurate interpretation and translation of results it is critical however, that phenotypic similarities and differences of DRG-derived cells lines are methodically compared to native neurons. Published reports to date show notable variability in how these DRG-derived cells are maintained and differentiated. Understanding the cellular and molecular differences stemming from different culture methods, is essential to validate past and future experiments, and enable these cells to be used to their full potential. This review describes currently available DRG-derived cell lines, their known sensory and nociceptor specific molecular profiles, and summarize their morphological features related to differentiation and neurite outgrowth.